(untitled) (Research, Society and Development, 2021)
Perinatal asphyxia is defined as na injury to the newborn, characterized by oxygen deprivation (hypoxia) and perfusion disorder, which can produce multiple systemic repercussions. Hypoxic-ischemic encephalopathy is the most serious consequence of perinatal asphyxia and is among the main causes of perinatal mortality and morbidity. Currently, therapeutic hypothermia, also called induced, presents itself as a neuroprotective therapy capable of reducing mortality and improving the neurological outcome in this clientele, however the success of therapy requires the training of nurses, in order to provide qualified and safe care. This study aims to describe, according to the literature, the nursing care provided to the newborn submitted to therapeutic hypothermia. It is na integrative review carried out between September and October 2020, using electronic sources from the Virtual Health Library, PubMed, CINAHL, SCIELO, Web of Science and SCOPUS, with a time frame from 2015 to 2020. 1330 publications were found, of which 16 articles were included in the review according to the eligibility criteria established. Essential care: maintenance of central body temperature, hemodynamic monitoring, glycemic control, surveillance of the Integrated Amplitude Electroencephalogram, observation of the skin and communication with the ultid. Therapy has benefits, but its application depends on countless care involving the ultidisciplinar team. In addition, the breadth and relevance of the nurse’s performance during therapy became notorious, as nursing care is essential for maintaining treatment and preventing possible complications and adverse effects of therapeutic hypothermia.